Hubungan Budaya Patriarki dan Faktor Demografis Terhadap Pemilihan Jenis Kontrasepsi Pada Wanita Usia Subur di Kota Surabaya - Maheswari Hastoyo, Roro Patricia; Utomo, Budi; Jayanti, Ratna Dwi; Dwiningsih, Sri Ratna (Yayasan Jompa Research and Development, 2025)
The choice of contraceptive methods among women of reproductive age is influenced by various factors, including patriarchal culture and demographic characteristics such as age, education, and occupation. In urban areas like Surabaya, shifting social values and the accessibility of information and health services may affect reproductive decision-making patterns. This study aimed to analyze the relationship between patriarchal culture and demographic factors with the choice of contraceptive methods among women of reproductive age at Bulak Banteng and Pacarkeling Public Health Centers in Surabaya. This research employed an analytical observational design with a cross-sectional approach. A total of 96 respondents were selected using consecutive sampling. Data were collected through questionnaires and analyzed using the chi-square test with a significance level of p < 0.05. The results showed no significant relationship between patriarchal culture (p = 0.235), age (p = 0.156), education (p = 0.109), and occupation (p = 0.076) with contraceptive method choice. Most respondents had a low level of patriarchal culture, moderate education, were over 35 years old, and unemployed. In conclusion, patriarchal culture and demographic factors did not directly influence contraceptive choice. The decision to use contraception may be more affected by other factors beyond socio-demographic characteristics, such as service availability and access to reproductive health information.